Segmentación del turismo interno y del turismo receptivo en el Perú - Lazo Magallanes, Jesus Ricardo (2020)
Throughout my 20 years of work experience I have worked in the marketing areas of different companies in the textile, consulting, real estate and tourism sectors. It was within the tourism sector where I found the possibility of making a proper segmentation of domestic and inbound tourism in Peru, with the objectives of maximizing the profitability of marketing investment, better understanding the travel markets and communicate the country's offer more effectively to tourists. The final result was a segmentation by travel group, life cycle and lifestyle.